Effect of Toxoplasmosis on Lipid Profile and Thyroid Hormones in Aborted Women - Al-Khamesi, Maisam Balasim (Al-Nahrain Journal of Science, 2018)
This study addressed the effect of toxoplasmosis on levels of thyroid hormones (Triiodothyronine [T3], Thyroxine [T4] and Thyroid Stimulating Hormone [TSH], and lipid profile such as (Cholesterol, Triglycerides, High-Density Lipoprotein [HDL], Low-Density Lipoprotein [LDL] and very Low -Density Lipoprotein [vLDL] in 100 samples which included 80 aborted women, who had positive test for toxoplasmosis and 20 samples act as control group during the period from August 2015 to January 2016 which were taken from Al-Yarmouk Teaching Hospital in Baghdad City. Infected and control women had similar age that ranged between (17-47) years old. Serum samples were collected and tested by ELISA technique, lipid profile tests were performed by using commercial kits, in addition to measured thyroid hormones by using the Mini Vidus apparatus. The results revealed chronic infection [IgG] recorded the highest percentage (68.75%) and the acute infection [IgM] showed the lowest percentage (31.25%). There were significant decrease in the total cholesterol, Triglycerides, LDL and vLDL (110.96±1.55, 30.93±0.56, 41.38 ±1.55 & 6.40 ±0.18 mg/dl respectively) compared with control group (200.05 ±5.83, 56.05 ±1.98, 142.85±2.05 & 36.90±1.24 mg/dl respectively). On the other hand, a significant increase in HDL, T3 and TSH was recorded (64.51±1.27 mg/dl, 12.74 ±0.53 and 11.64±0.58 mlU/L respectively) compared with control group (53.45±1.57 mg/dl, 1.49 ±0.16 & 2.29 ±0.25 mlU/L respectively). A significant decline in T4 was estimated (2.81±0.12 mlU/L) compared with control group (8.35±0.80 mlU/L). So, we concluded that the Toxoplasma gondii had important role in changes of lipid profile levels & thyroid hormones in infected women